The Double‐Faced Nature of Hydrogen Bonding in Hydroxy‐Functionalized Ionic Liquids Shown by Neutron Diffraction and Molecular Dynamics Simulations. Issue 37 (9th July 2019) - Niemann, Thomas; Neumann, Jan; Stange, Peter; Gärtner, Sabrina; Youngs, Tristan G. A.; Paschek, Dietmar; Warr, Gregory G.; Atkin, Rob; Ludwig, Ralf
Abstract: We characterize the double‐faced nature of hydrogen bonding in hydroxy‐functionalized ionic liquids by means of neutron diffraction with isotopic substitution (NDIS), molecular dynamics (MD) simulations, and quantum chemical calculations. NDIS data are fit using the empirical potential structure refinement technique (EPSR) to elucidate the nearest neighbor H⋅⋅⋅O and O⋅⋅⋅O pair distribution functions for hydrogen bonds between ions of opposite charge and the same charge. Despite the presence of repulsive Coulomb forces, the cation–cation interaction is stronger than the cation–anion interaction. We compare the hydrogen‐bond geometries of both "doubly charged hydrogen bonds" with those reported for molecular liquids, such as water and alcohols. In combination, the NDIS measurements and MD simulations reveal the subtle balance between the two types of hydrogen bonds: The small transition enthalpy suggests that the elusive like‐charge attraction is almost competitive with conventional ion‐pair formation. Abstract : Two sides of the story : The double‐faced nature of hydrogen bonding has been observed in hydroxy‐functionalized ionic liquids by means of neutron diffraction with isotopic substitution (NDIS), molecular dynamics (MD) simulations, and quantum chemistry. Two types of hydrogen bonds exist: common hydrogen bonds between cations and anion as well as unusual hydrogen bonds between cations.